Predictors of achievement in sports among successful Pakistani female athletes (IR) - Naseer, Abida (2017)
The present study aims to examine the influence of social support, social cultural, social personal and social interferential factors on the sports participation of successful female school athletes of Pakistan. The existing study employed a quantitative research approach using survey methodology. The questionnaire was composed for 313 randomly selected samples of successful female athletes from various secondary schools of rural areas in Pakistan. The survey data was analyzed using descriptive statistics, correlation, multiple regression and path analyses. The findings revealed that social support, social cultural, social personal, and social interferential factors significantly predicted the variance in sports participation of successful female athletes. Furthermore, the path analysis results indicated that social interferential factor as moderator in the models did not influence the relationships of social support, social cultural, and social personal factors with the sports participation in path model. The findings revealed that all variables of social support, social cultural, and social personal factors established positive significant relationships with sports participation of successful female athletes. However, social interferential factor had negative significant association. It was found that social support, social cultural, and social personal factors have positive low effect than the negative effect of social interferential factor on sports participation. The implication of the study suggest that siblings and peers should provide positive and energetic support as well as school management should developed sports facilities and female sport associations should raise the issue to higher authorities on women sport environment for equal opportunities to uplift the standards of sports participation in Pakistan at present.